Expansion and differentiation in higher education: the historical trajectories of the UK, the USA and France - Carpentier, V (Centre for Global Higher Education, University of Oxford, 2018)
Dr Vincent Carpentier from the UCL Institute of Education investigates expansion and differentiation in higher education, and the relationship between the two.